2003
DOI: 10.1111/j.1464-410x.2004.04546.x
|View full text |Cite
|
Sign up to set email alerts
|

Cavernosal nerve mapping: current data and applications

Abstract: There are four reviews in this month's section, two relating to the technical aspects of treating prostate cancer, one to genetic instability and bladder cancer, and the final one about continence surgery in urogenital prolapse. The authors are from Canada, the USA, and the UK. The messages from all of the reviews are clear, and provide interesting reading. The contributions to this section continue to give considerable information, and there are many more to follow.Although nerve‐sparing prostatectomy is wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…ED may stem from deficits in the vascular system, penile smooth muscles and autonomic nerves (Hecht et al, 2001). The integrity of cavernous nerve (CN) is critical for normal erectile function; even minor surgical impairment of this nerve can lead to impotence (Klotz, 2004; Walsh and Donker, 2002). The CN is principally composed of unmyelinated axons with a few scattered myelinated fibers (Schaumburg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ED may stem from deficits in the vascular system, penile smooth muscles and autonomic nerves (Hecht et al, 2001). The integrity of cavernous nerve (CN) is critical for normal erectile function; even minor surgical impairment of this nerve can lead to impotence (Klotz, 2004; Walsh and Donker, 2002). The CN is principally composed of unmyelinated axons with a few scattered myelinated fibers (Schaumburg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have supported the clinical efficacy of the CaverMap system to assist in cavernous nerve preservation. [42][43][44][45][46] However, other studies have questioned the usefulness of direct electrical stimulation and have recommended further refinements to the system. 47,48 In this study, direct stimulation was limited by anatomical restrictions associated with the sensor placement on the canine penis and an inability to quantify the erectile response with sequential ablation or at the time of cavernous nerve harvest.…”
Section: Plastic and Reconstructive Surgery • July 2006mentioning
confidence: 99%
“…The Cavermap TM device has been used as an adjunct to aid in identifying and preserving the cavernosal nerves. In a trial reported in 2000 [21], of 61 patients randomized to conventional nerve‐sparing or Cavermap‐assisted nerve‐sparing procedure there tended to be better potency after its use, with a significant difference in potency outcomes as assessed by nocturnal Rigiscan TM testing. However, others have reported less satisfaction with the device and its outcomes, citing difficulties with the reliability of the technique and its poor correlation with long‐term potency outcomes as problems with its implementation [22–24].…”
Section: Clinical Applicationsmentioning
confidence: 99%